Appropriateness of Western-Style HRM practices to emerging countries, a case study of Bangladesh - Jantan, Amer Hamzah; Islam, Md Asadul; Hashim, Haslinda; Choo, Wei Chong (Universiti Putra Malaysia Press, 2018)
This paper outlines its significance to the both academic and practice arena. The main question, therefore, underpinning this paper and research inform it is: • How appropriate the Western-Style HRM practices to the emerging countries specifically in Bangladesh.